Local electronic government : a comparative study - Drüke, Helmut (London ; New York : Routledge, 2005)
This book investigates how the internet is being used as a tool for comprehensively modernizing local government.
Urban e-government in Finland / Ari-Veikko Anttiroiko -- Local e-government in France / Jean Pierre Chamoux -- Local e-government in Germany / Helmut Drüke -- Local e-government in the Netherlands / Roland Leenes and Jörgen Svensson -- E-government in the United Kingdom / Martin Ferguson -- E-public administrative process in Japan / Masahiro Fujita, Takahiro Izawa, and Hiroki Ishibashi -- American local governments : confronting the e-government challenge / Mary Maureen Brown and Shannon Schelin -- Concluding remarks on national specifics and transfer and adoption of good practice / Helmut Drüke.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Internet in public administration; Local government; Comparative government; Local Government; Internet dans l'administration publique; Administration locale; local government; POLITICAL SCIENCE -- Public Affairs & Administration; Comparative government; Internet in public administration; Local government; Multi-User.